Odpowiedź :
Odpowiedź:
a)
3x+ 2 = 2x + 1
3x- 2x = 1 - 2
x = - 1
b)
4x - 3 = 3 - 2x
4x + 2x = 3 + 3
6x = 6
x = 6/6 = 1
c)
3x- 2 = - 1 - 2x
3x+ 2x = - 1 + 2
5x = 1
x = 1/5
d)
- 3x + 7 = - 5x + 3
- 3x + 5x = 3 - 7
2x = - 4
x = - 4/2 = - 2
e)
3(x + 1) + x = 2x
3x + 3 + x = 2x
4x + 3 = 2x
4x - 2x = - 3
2x = - 3
x = - 3/2 = - 1 1/2
f)
2(x + 1) + 1 = 2x + 3
2x + 2 + 1 = 2x + 3
2x + 3 = 2x + 3
2x + 2x = 3 - 3
0 = 0
Równanie tożsamościowe , spełnia je każda liczba ze zbioru liczb rzeczywistych
x ∈ R
g)
3(2x + 4) - 4x = 2 - 2(x + 1)
6x + 12 - 4x = 2 - 2x - 2
2x + 12 = - 2x
2x + 2x = - 12
4x = - 12
x = - 12/4 = - 3
h)
8(3x - 4) + 2 = 5 - 7(x + 5)
24x - 32 + 2 = 5 - 7x - 35
24x - 30 = - 7x - 30
24x + 7x = - 30 + 30
31x = 0
x = 0